Mitigation of methane production from ruminants; effect of nitrate and urea on methane production in an in vitro system and on growth performance and methane emissions in growing cattle : - Inthaphanya, Sangkhom (Can Tho University, 2012)
Cassava leaf meal plus urea, Cassava leaf meal plus calcium nitrate, mimosa pigra leaf meal plus urea and mimosa leaf meal plus calcium nitrate